2012
DOI: 10.1016/j.ijrobp.2012.07.2362
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Interaction of Heart and Lung in Thoracic Irradiation

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 21 publications
4
92
0
Order By: Relevance
“…Published reports using rats have demonstrated that while irradiation of the heart and lung induce cardiac and pulmonary dysfunction, respectively, whole-thoracic lung irradiation results in significantly enhanced morbidities (27,28). Clinical studies have also demonstrated that incidental irradiation of the heart increases the risk of radiation-induced pneumonitis in patients receiving radiotherapy for non-small cell lung cancer (NSCLC) (29).…”
Section: Discussionmentioning
confidence: 99%
“…Published reports using rats have demonstrated that while irradiation of the heart and lung induce cardiac and pulmonary dysfunction, respectively, whole-thoracic lung irradiation results in significantly enhanced morbidities (27,28). Clinical studies have also demonstrated that incidental irradiation of the heart increases the risk of radiation-induced pneumonitis in patients receiving radiotherapy for non-small cell lung cancer (NSCLC) (29).…”
Section: Discussionmentioning
confidence: 99%
“…The special importance of the primary injury to the EC for radiation-induced late toxicity in the lungs is emphasized by studies on pulmonary arterial hypertension (PAH), where a functional impairment or even partial loss of the EC could be detected immediately after a selective lung irradiation and long before the manifestation of the first clinical symptoms (33). In this study, we show now that adoptive transfer of MSCs within the early phase after irradiation also provides long-term protection from radiation-induced EC damage, EC loss, and immune cell infiltration that translates in protection from fibrosis development.…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thementioning
confidence: 99%
“…There are concerns about the acute and late pulmonary and cardiovascular toxicity, especially for patients with a medical history of cardiovascular and/or pulmonary disease [4,5].…”
Section: Introductionmentioning
confidence: 99%